2022
DOI: 10.1111/ggi.14366
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of muscle quantity, quality and function measurements in hospitalized older adults

Abstract: Acute sarcopenia is defined by the development of incident sarcopenia (low muscle quantity/quality and function) within 6 months of a stressor event. However, outcome measures for clinical trials have not been validated. This study aimed to characterize changes in muscle quantity, quality, strength, and physical function during and after hospitalization.Methods: Patients aged ≥70 years admitted for elective colorectal surgery, emergency abdominal surgery or acute infections were recruited from a single univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In fact, short- to medium-term interventions, such as interventions that last 8–10 wks, do not alter IMAT 24,27 . Moreover, a similar design to the present study was reported to examine muscle mass and quality (identified by the phase angle) using the impedance method, but as in the present study, insufficient improvement in skeletal muscle mass was obtained 28 . Thus, it is possible that exercise does not actually reduce IMAT, but it prevents it from increasing 18 .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In fact, short- to medium-term interventions, such as interventions that last 8–10 wks, do not alter IMAT 24,27 . Moreover, a similar design to the present study was reported to examine muscle mass and quality (identified by the phase angle) using the impedance method, but as in the present study, insufficient improvement in skeletal muscle mass was obtained 28 . Thus, it is possible that exercise does not actually reduce IMAT, but it prevents it from increasing 18 .…”
Section: Discussionmentioning
confidence: 51%
“…24,27 Moreover, a similar design to the present study was reported to examine muscle mass and quality (identified by the phase angle) using the impedance method, but as in the present study, insufficient improvement in skeletal muscle mass was obtained. 28 Thus, it is possible that exercise does not actually reduce IMAT, but it prevents it from increasing. 18 The same is true for skeletal muscle mass, 27 and long-term interventions are essential for maintaining muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Welch et al, reported decreasing SMM after one week of hospitalization, but it was not significant [36]. Only Aarden et al compared muscle index, and found that there was no change in mean of skeletal muscle mass index PLOS ONE [32,34,36] demonstrated that hand grip strength of participants reduced on discharge, however not adequate to be statistically significant. Aarden et al [31] reported slight increase (0.1kg) in mean hand grip strength on discharge, but statistical significance was not reported.…”
Section: Sarcopenia During Hospitalizationmentioning
confidence: 99%
“…The mean age for all the participants were 78.1 years. The studies involved participants recruited from geriatric medicine wards [31,35], general medical wards [32,[34][35][36], surgical wards [36] and cardiology wards [31,33] Mean duration of stay for the study participants were 14 days. Details of demographic particulars of included studies are presented in Table 1.…”
Section: Included Studiesmentioning
confidence: 99%
“…Understanding acute changes in muscle and performance measures in a heterogeneous population of older hospitalised patients relies on sensitivity to change in these measures. There are few studies on such changes that are still poorly understood [42].…”
Section: Diagnosing Sarcopenia In Acute Carementioning
confidence: 99%